DETERMINATION OF CUTTING SPEED VALUES FOR PROCESSING A NON-RIGID SHAFT - Shakenova Zhamila Nauryzbaevna (Scientific Journal of Pedagogy and Economics, 2020)
This article discusses the flexibility of the technological system due to the influence of external shear forces on it during processing of non-rigid parts such as bodies of revolution. In order to reduce the deformation of the part during the Py cutting force is applied to it, various fastening schemes are used and, accordingly, calculations are made on the rationality of its choice. The bending moments M1 and M2 in sections Z1 and Z2 are determined in an analytical way (curve part). The cutting force is calculated according to the formula (1), and also according to formulas (2) and (3) there are determined the points of maximum and minimum deflection of the non-rigid shaft. By transforming formulas (1), (2) and (3), the formulas (4), (5) and (6) were derived. Using formula (4), the values of the cutting speed V along the entire length of the shaft part L were calculated, and the cutting force Py at each fixed point Z1 to Z21 was determined from the obtained expressions (5) and (6). The block diagram and software implementation in the Delphi XE8 environment are presented in which calculations are performed so that the minimum value of the shaft deflection always has a constant value y=const. A graphical dependence of the change in cutting force on the values of the cutting speed is obtained. The developed subsystem will also allow to visually display how you can avoid various errors during the machining of a non-rigid part (shaft).